1980
DOI: 10.1113/jphysiol.1980.sp013087
|View full text |Cite
|
Sign up to set email alerts
|

Renal function in conscious rats after indomethacin. Evidence for a tubular action of endogenous prostaglandins.

Abstract: SuMMARY1. Conscious rats, with implanted carotid arterial cannulae, received a saline infusion (5.8 ml./hr) via a tail vein for a 6 hr period. The urinary excretion of water, sodium, potassium, urea and the osmolal output were monitored, together with the systemic blood pressure. Glomerular filtration rate (inulin clearance) and effective renal plasma flow (p-aminohippurate clearance) were also measured. Four hours after the start of the infusion, indomethacin (10 mg/kg body weight) in buffered saline, or buff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
27
2

Year Published

1980
1980
2005
2005

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 36 publications
9
27
2
Order By: Relevance
“…Several mechanisms have been suggested to account for the natriuretic and diuretic properties of prostaglandins, including an increase in total renal blood flow, and its distribution to the medulla (McGiff & Malik, 1976), antagonism of the action of antidiuretic hormone (Berl et al 1977), or a more direct action on the renal tubule (Roman & Kauker, 1978;Haylor & Lote, 1980).…”
Section: Introductionmentioning
confidence: 99%
“…Several mechanisms have been suggested to account for the natriuretic and diuretic properties of prostaglandins, including an increase in total renal blood flow, and its distribution to the medulla (McGiff & Malik, 1976), antagonism of the action of antidiuretic hormone (Berl et al 1977), or a more direct action on the renal tubule (Roman & Kauker, 1978;Haylor & Lote, 1980).…”
Section: Introductionmentioning
confidence: 99%
“…The reason for the small changes may be due to the dose used, which might be somewhat low for this species, although our earlier study with naproxen, using a similar human dose, revealed significant increases in urine flow (17). Although studies with higher doses could help clarify this, indomethacin, nevertheless, has been shown to decrease urine output in conscious rats (13,18). This effect of indomethacin on urine flow has been attributed to its ability to inhibit prostaglandin synthesis, in particular prostaglandin E 2 (PGE 2 ), which inhibits vasopressin-stimulated water reabsorption in the collecting duct via EP3 receptor activation (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…Non-myelinated axons (diameter 0-15-0-82 fum) with varicose terminals (serially sectioned) were identified as being (i) typically noradrenergic (cf. Ballard, 1978) In the conscious rat, the ability of indomethacin to increase the renal concentration gradient and reduce urine flow in the absence of changes in renal haemodynamics has been explained by prostaglandin synthetase inhibition altering renal tubular reabsorption at a distal nephron site (Haylor & Lote, 1979, 1980. In the present experiments we have investigated the action of PGE2 on renal function, and on the corticomedullary sodium gradient, in anaesthetized rats.…”
Section: P Physiological Society December 1979mentioning
confidence: 99%